Novel Modular Walking Orthosis (MOWA) for Powerful Correction of Gait Deviations in Subjects with a Neurological Disease - Jan-Hagen Schröder; Gion A. Barandun; Pascal Leimer; Rafael Morand; Beat Göpfert; Erich Rutz (MDPI AG, 2023)
This article introduces a novel concept where advanced technologies have been leveraged to produce a modular walking orthosis (MOWA) within a completely digital process chain. All processes of this new supply chain are described step-by-step. The prescription and treatment of lower leg orthoses for individuals with paralysis or muscle weakness, particularly cerebral palsy (CP), are complex. A single case study indicates successful treatment with this new orthosis (MOWA). From the authors' perspective, this innovative fitting concept is promising and will contribute to creating more efficient care within a multidisciplinary team.